Export Diversification of Nepal: Policy Context and Impacts - KC, Raj Kumar (Nepalese Journal of Management Science and Research, 2019)
This study aims at examining the extent of diversification attained in trade relationships of Nepal, identify factors responsible for the situation and come out at suggestive package to foster more sustainable and contributing trading relationships to maximize the benefits for the country. Studies have revealed that insufficient export diversification has virtually dragged the economy in total disarray due to defect in government policies. The developed world relies heavily on the exchange of goods and services for faster and sustainable economic progress. Trade has been a priority from the very beginning of the First Five-Year Plan in 1956, but it has failed to move ahead owing to lack of technology, appropriate policy measures and sufficient priority given to it. The secondary analysis showed that the volume of trade has been continuously increasing with economic liberalization in the aftermath of 1990. However, the volume of exports has remained too meager to sustain Nepal’s imports. Therefore, the volume of trade deficit is ever widening. Reforms to expedite exports that began in the late seventies have failed to yield a positive outcome in the national economy. The liberalization of eighties, nineties and membership of World Trade Organization (WTO) have failed to ensure a sustained diversified trading structure both in terms of products and services and trading partners. Growing dependency on India has been one of the major challenges in the economy.